2006
DOI: 10.2460/ajvr.67.3.392
|View full text |Cite
|
Sign up to set email alerts
|

Median effective dose of isoflurane, sevoflurane, and desflurane in green iguanas

Abstract: Over time, MACs decreased for all 3 agents. Final MAC measurements were similar to values reported for other species. The decrease in MACs over time may be at least partly explained by limitations of anesthetic uptake and distribution imposed by the reptilian cardiorespiratory system. Hence, for a constant end-tidal anesthetic concentration in an iguana, the plane of anesthesia may deepen over time, which could contribute to increased morbidity during prolonged procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 42 publications
1
26
0
3
Order By: Relevance
“…The first M A C is o f lu ra n e , determined at >4hr post-induction, was 2.4 ± 0.7% , and is higher than the values obtained in both the M o sley , e t al, stu d y an d o u rs. T he se c o n d an d th ird M A C is o f lu ra n e determinations (Barter, et al, 2006) were lower and suggested a decrease o f minimum alveolar concentration values over time, but comparison o f these later values with ours is problematic. By definition, minimum alveolar concen tration should stay the sam e over tim e i f the stim ulus is supramaximal and other factors are kept constant, which the authors reported (Merkel and Eger, 1963).…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…The first M A C is o f lu ra n e , determined at >4hr post-induction, was 2.4 ± 0.7% , and is higher than the values obtained in both the M o sley , e t al, stu d y an d o u rs. T he se c o n d an d th ird M A C is o f lu ra n e determinations (Barter, et al, 2006) were lower and suggested a decrease o f minimum alveolar concentration values over time, but comparison o f these later values with ours is problematic. By definition, minimum alveolar concen tration should stay the sam e over tim e i f the stim ulus is supramaximal and other factors are kept constant, which the authors reported (Merkel and Eger, 1963).…”
Section: Discussionmentioning
confidence: 83%
“…Two minimum alveolar concentration determinations studies conducted six or more days apart on the same experimental group o f igua nas yielded minimum alveolar concentration values o f 2.0 ± 0.6% and 2.1 ± 0.6% (Mosley, et al, 2003). In a different study, M A C is o f lu r a n e determinations made on the same ani m als d u rin g a sin g le a n e s th e s tic e p is o d e th a t la s te d approximately 10 horns, yielded the following results: 2.4 ± 0.7%, at about four to fives hours post induction (PI), 2.1 ± 0.5 % at eight to nine hours PI, and 1.8 ± 0.3% at 10 -11 hr PI; (Barter, et al, 2006). In the latter study minimum alveolar concentration values were initially high and only decreased over tim e to levels com parable to those o f M osley, et al, (2003) experiment.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations